The Association between Medication Adherence Level with Success of Therapy in Hypertension Patients - Galuh Wulanjari; Lusia Murtisiwi; Rizqi Nurul Khasanah (GLOBAL HEALTH SCIENCE GROUP, 2023)
The success of therapy in hypertensive patients is influenced by drug use adherence behavior. The success of therapy reduces the risk of complications in other organs and reduces mortality. This study aims to determine the association between the level of adherence to the use of antihypertensive drugs in patients with the success of therapy. Adherence data was collected using the Hill-Bone Translate Indonesia 11 (HBTS-I 11) questionnaire and the therapeutic success data were taken from medical records in hypertensive patients at the outpatient pharmacy installation at UNS Hospital. This research is observational through a cross sectional approach. The sampling technique was carried out by purposive sampling technique by applying the inclusion criteria of respondents. Data collection was carried out by approaching potential patients in the waiting room of the UNS Hospital outpatient pharmacy installation to be given the Hill-Bone translate Indonesia-11 questionnaire. Respondents’ willingness to participate in the study was proven by their willingness to fill out informed consent. The analysis test of the association between drug adherence and the success of achieving the therapeutic target was carried out with the Chi Square test. The results of the study showed that patients who adhered to using drugs were 41% and those who were not adhered were 59%. The Chi Square test analysis showed that p value = 0.005 (p <0.05) indicating there was a significant association between adherence to taking antihypertensive drugs and the success of therapy for hypertensive patients in the outpatient pharmacy installation at UNS Hospital.